Digital Marketing Strategies and their Role in Enhancing the Strategic Capabilities of the Bank's Sector in Erbil Governorate - Abduljabbar Agha Yaseen Akram; Khairi Ali Auso (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The main purpose of this research is to examine digital marketing strategies and their role in enhancing the strategic capabilities of the bank sector in the Erbil Governorate. The research used the qualitative method to obtain data and classify the study problem, by exploring several questions and concentrating on the relational impact, and variance between research variables. In this regard, a conceptual model is considered and formed three main hypotheses. For data analysis, statistical tests are used namely, correlation test, and regression analysis. The survey was used to obtain data from bank managers such as bank general managers, CEOs, marketing managers, sales managers, and branch managers. A sample of (245) managers participated in the survey by replying to the survey questions, finally, (233) questionnaire forms were obtained for examination and conduct statistical analysis methods through SPSS version 25. Results of correlation analysis showed that digital marketing strategies jointly, and exclusively have a positive and significant relationship with strategic capabilities based on bank managers' perceptions. Results demonstrated that digital marketing strategies positively impacted strategic capabilities. Results showed that attracting clients, communication, client participation, learning strategy, and retaining clients through digital channels positively and significantly impacted strategic capabilities. Furthermore, results showed there were no variances in digital marketing strategies and strategic capabilities according to the bank managers' profiles such as gender, age, level of education, job position, and overall banking experience